Psychological assessment of disordered thinking and perception - Weiner, Irving B.; Kleiger, James H., 1952- (American Psychological Association, 2021)
"This essential single-source guide to multimethod psychological assessment of disordered thinking and perception offers practical insights for applying key evaluation measures and strategies, along with important contextual considerations. It provides mental health professionals with valuable empirical and interpretive support as they answer assessment questions for diagnostic and decision-making purposes. Chapters are written by renowned assessment psychologists recognized for their expertise and contributions in developing and researching specific assessment instruments or topics. They provide up-to-date information about widely used self-report measures and interview techniques, performance-based tests, and cognitive and neuropsychological measures, including their conceptual basis, psychometric properties, empirical support, and key interpretive elements. Additional chapters review special developmental and cross-cultural considerations, as well as guidelines for forensic assessments. Two in-depth case examples provide comprehensive illustrations of the multimethod evaluation process with an adolescent and an adult"--